2022
DOI: 10.1097/spv.0000000000001159
|View full text |Cite
|
Sign up to set email alerts
|

Failure Rate of Retropubic Midurethral Sling With and Without Concomitant Robotic Sacrocolpopexy

Abstract: Importance:The retropubic midurethral sling (rMUS) and sacrocolpopexy are treatments for stress urinary incontinence (SUI) and pelvic organ prolapse, respectively, which are often performed concomitantly. Objective:The purpose of this study was to identify whether a difference exists in the failure rates of rMUS when placed alone or at the time of robotic sacrocolpopexy (RSC). Study Design:We conducted a single-center retrospective cohort study of patients who underwent rMUS placement between December 2015 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Separate models were run to estimate cost-utilities for 6 different scenarios: Separate models were generated based on surgical approach, given the anatomic differences and varying postoperative SUI rates between the 2 types of surgical procedures. 7,15,16 Women were considered to have preexisting SUI if subjective and objective signs of SUI were present, and those without preexisting SUI had no subjective or objective complaints. The International Continence Society definition of occult SUI was used and includes visible urinary leakage with prolapse reduction in women without subjective complaints of SUI.…”
Section: Materials and Methods Decision Tree Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Separate models were run to estimate cost-utilities for 6 different scenarios: Separate models were generated based on surgical approach, given the anatomic differences and varying postoperative SUI rates between the 2 types of surgical procedures. 7,15,16 Women were considered to have preexisting SUI if subjective and objective signs of SUI were present, and those without preexisting SUI had no subjective or objective complaints. The International Continence Society definition of occult SUI was used and includes visible urinary leakage with prolapse reduction in women without subjective complaints of SUI.…”
Section: Materials and Methods Decision Tree Modelmentioning
confidence: 99%
“…Separate models were generated based on surgical approach, given the anatomic differences and varying postoperative SUI rates between the 2 types of surgical procedures 7,15,16 . Women were considered to have preexisting SUI if subjective and objective signs of SUI were present, and those without preexisting SUI had no subjective or objective complaints.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Long-term outcome studies have also demonstrated a high rate of successful treatment, with fewer than 9% of patients undergoing concomitant midurethral sling at the time of POP repair requiring subsequent retreatment for SUI. 5,6…”
mentioning
confidence: 99%